Manajemen Pendidikan Anak Usia Dini di TK Bunda Wardah Kecamatan Bacukiki Barat Kota Parepare - Sri Hasnawati; Muhammad Jufri (PT FORMOSA CENDEKIA GLOBAL, 2022)
The background of this research is that early childhood management is very important and BUNDA WARDAH Kindergarten already has good management. Based on this background, the authors are interested in conducting research that examines the management of early childhood education in Bunda Wardah Kindergarten, West Bacukiki District, Parepare City. The formulation of the problem in this study is